2021
DOI: 10.30536/j.ijreses.2020.v17.a3387
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Analysis of Surface Urban Cool Island Using Thermal Infrared Imagery of Salatiga City, Indonesia

Abstract: The detection and monitoring of the dynamics of urban micro-climatesneeds to be performedeffectively, efficiently, consistently and sustainably inan effort to improve urban resilience to suchphenomena. Thermal remote sensing posesses surface thermal energy detection capabilities which can be converted into surface temperatures and utilised to analyse the urban micro-climate phenomenon overlarge areas, short periods of time, and at low cost. This paper studies the surface urban cool island (SUCI) effect, the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…This fact is relevant to studies on sustainable agriculture in Central Java due to soil capability and the need for support regulation of physically and economically [16]. Another study showed that land cover changes to built-up areas impact the surface urban heat island in Salatiga City [17].…”
Section: Regionmentioning
confidence: 93%
“…This fact is relevant to studies on sustainable agriculture in Central Java due to soil capability and the need for support regulation of physically and economically [16]. Another study showed that land cover changes to built-up areas impact the surface urban heat island in Salatiga City [17].…”
Section: Regionmentioning
confidence: 93%
“…The stratified random sampling approach was used for the sampling process. The SUHI and SUCI thresholds were determined using earlier research carried out by [10] after image processing to assess the density of buildings, vegetation, and surface temperature in the city of Bandung. Then, to determine the direction of the link and its influence, regression and correlation tests were run, as described by [8] The land-use pattern surrounding a UCI, particularly proximity to hot spots or bodies of water, may influence its intensity, as context temperature has a cumulative effect.…”
Section: Methodsmentioning
confidence: 99%
“…Normal conditions or areas designated as normal are necessary to ascertain the distribution and trend of SUCI surface temperature thresholds and surface temperature readings. In the region denoted by SUCI, the equation can reach the threshold value: 𝑇 𝑆𝑈𝐶𝐼 < 𝜇 𝑛𝑜𝑟𝑚 + 0,5𝛼 𝑛𝑜𝑟𝑚 (10) Description : 𝑇 𝑆𝑈𝐶𝐼 : Surface temperature indicated by SUCI (°C) 𝜇 𝑛𝑜𝑟𝑚 : average surface temperature of the image under normal conditions (°C) 𝛼 𝑜𝑟𝑖 : standard deviation of image under normal condition Thus, the intensity of SUCI can be measured using a formula based on a modification of the equation found in the study. [16] :…”
Section: Urban Cool/heat Island Area Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Satelit ini mampu mendeteksi perubahan tutupan lahan secara temporal, karena telah memiliki 9 generasi. Perubahan tutupan lahan yang terjadi di Kecamatan Sungai Raya saat masih menjadi wilayah Kabupaten Pontianak hingga menjadi ibukota Kabupaten Kubu Raya, dapat diindera dengan satelit Landsat (Dewantoro et al, 2020).…”
Section: Kecamatanunclassified